Editorial: AABFJ Volume 11, Issue 4, 2017 - Elvia Shauki; Harun Harun; Habib Khan (Australasian Accounting, Business and Finance Journal, 2017)
Editorial AABFJ.
Keywords: Editorial AABFJ; special issue; Universitas Indonesia